Three-Dimensional Thermal Analysis of Three-Phase Enclosed GIS Bus Bars - Hongtao Li; Naiqiu Shu; Ling Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The ampacity of GIS bus bars is limited by the maximum operation temperature of the contacts. This paper employs the coupled eddy current, fluid and thermal finite-element method (FEM) to solve the three-dimensional (3-D) heat transfer problem in a three-phase enclosed GIS bus bar. The contact resistance is considered and described as a resistor between the conductor and the contact finger. In order to avoid convective boundary condition on the tank surface which is not easy to apply, the ambient air is introduced into the solution region. The temperature dependent thermal properties of SF6 gas and air are considered. The temperatures calculated by proposed model are found to be in good agreement with the experimental data of a 126 kV three-phase enclosed bus bar prototype.